2021
DOI: 10.1007/s40801-021-00248-5
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Assessment of Interferon-β-1b and Interferon-β-1a Adherence Before and After the Introduction of the BETACONNECT® Autoinjector: A Retrospective Cohort Study

Abstract: Background Both interferon beta-1b (IFN-β-1b) and interferon beta-1a (IFN-β-1a) are immunomodulators that require regular subcutaneous self-administration by patients with multiple sclerosis (MS). However, no electronic autoinjector is available for IFN-β-1a in the US. Objective This retrospective cohort study investigated adherence to two subcutaneous disease-modifying therapies, IFN-β-1b and IFN-β-1a, during two periods (before and after the introduction of the BETACONNECT ® autoinjector for IFN-β-1b). Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…BETACONNECT, RebiSmart, ExtaviPro) showed that the BETACONNECT device was preferred [ 29 ]. Recently, a retrospective cohort study conducted in the USA found that after the introduction of BETACONNECT, adherence to interferon β-1b was higher than for patients taking interferon β-1a without an electronic auto-injector, and that more than 90% of patients using BETACONNECT had ≥ 90% medication possession ratio, a threshold commonly used to define good adherence [ 30 ]. In a further recent study, patient satisfaction with the BETACONNECT device was maintained over 2 years, with median scores of 9 out of 10 both at baseline and at the end of the study period [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…BETACONNECT, RebiSmart, ExtaviPro) showed that the BETACONNECT device was preferred [ 29 ]. Recently, a retrospective cohort study conducted in the USA found that after the introduction of BETACONNECT, adherence to interferon β-1b was higher than for patients taking interferon β-1a without an electronic auto-injector, and that more than 90% of patients using BETACONNECT had ≥ 90% medication possession ratio, a threshold commonly used to define good adherence [ 30 ]. In a further recent study, patient satisfaction with the BETACONNECT device was maintained over 2 years, with median scores of 9 out of 10 both at baseline and at the end of the study period [ 31 ].…”
Section: Discussionmentioning
confidence: 99%